Gravity-driven deep-reaching deformations and large-scale landslides in recently uplifted mountain areas: the case-study of mt. cucco and belpiano (ligurian apennine, italy) - Faccini, Francesco; Robbiano, Andrea; Raso, Emanuele; Roccati, Anna (Italian journal of engineering geology and environment, 2013)
<span data-sheets-value=""1":2,"2":"This work concerns with a DSGSD located in upper Sturla Valley (Northern Apennines, Italy), in the Municipality of Borzonasca, in an recently uplifted mountain area where the historic Belpiano hamlet was settled. The investigation of DSGSD was carried out through field survey, historic maps comparison, drilling and monitoring activities; seismic surveys were carried out in order to define the depth of the bedrock not involved in the DSGSD. The DSGSD origin is related to the slope particular geological structure with hard, fractured sandstones overlaying weak shales and characterized by a consequent high groundwater circulation supported by large amounts of rainfall, typical of this geographic area. Other DSGSDs have been studied and registered in this particular geological contest of Northern Apennines, actually in the Gottero Unit areas belonging to the upper Sturla Valley. Clear morphotectonic and geomorphological elements of activity have been detected, in addition to rock blocks detached by the bedrock and sliding masses related to active landslides. The most significant phenomenon is the landslide which involved the ancient parish church of Belpiano during XVII century; another event occurred in 1982 when a heavy rainfall greater than 600 mm over 5 days caused a hydrogeological disaster involving the whole Sturla Valley. Because of the large amount of rock and debris (ranging 320-480 millions of cubic meters) forming the sliding mass potentially affected by DSGSD and taking in consideration the erosional activity of Sturla river at the bottom of the slope and the actual climate changes it's reasonable to suppose that a reactivation, even partial, of DSGSD could create a landslide lake along the Sturla stream and a consequent high risk for several thousand people living downstream in the villages of Borzonasca, Mezzanego and Carasco"" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">This work concerns with a DSGSD located in upper Sturla Valley (Northern Apennines, Italy), in the Municipality of Borzonasca, in an recently uplifted mountain area where the historic Belpiano hamlet was settled. The investigation of DSGSD was carried out through field survey, historic maps comparison, drilling and monitoring activities; seismic surveys were carried out in order to define the depth of the bedrock not involved in the DSGSD. The DSGSD origin is related to the slope particular geological structure with hard, fractured sandstones overlaying weak shales and characterized by a consequent high groundwater circulation supported by large amounts of rainfall, typical of this geographic area. Other DSGSDs have been studied and registered in this particular geological contest of Northern Apennines, actually in the Gottero Unit areas belonging to the upper Sturla Valley. Clear morphotectonic and geomorphological elements of activity have been detected, in addition to rock blocks detached by the bedrock and sliding masses related to active landslides. The most significant phenomenon is the landslide which involved the ancient parish church of Belpiano during XVII century; another event occurred in 1982 when a heavy rainfall greater than 600 mm over 5 days caused a hydrogeological disaster involving the whole Sturla Valley. Because of the large amount of rock and debris (ranging 320-480 millions of cubic meters) forming the sliding mass potentially affected by DSGSD and taking in consideration the erosional activity of Sturla river at the bottom of the slope and the actual climate changes it's reasonable to suppose that a reactivation, even partial, of DSGSD could create a landslide lake along the Sturla stream and a consequent high risk for several thousand people living downstream in the villages of Borzonasca, Mezzanego and Carasco